Ismail Bouderbah's travel to Ghat in 1858, its objectives, and results in the French occupation's strategy of incursion into the desert - Kadida, محمد مبارك (The Algerian Historical Journal, 2026)
This research is studying the travel of Ismail Bouderbah to Ghat in 1858, one of the most important trips made by one of the most important translators who adopted the French occupation in the desert in a period did not have sufficient information about the desert and special touaregs tribes, This trip from Laghouat to Ghat specially targeted information collection and work on the possibility of signing a commercial agreement with a service for the expansionist strategy for the French occupation